Survey of applications of WBG devices in power electronics - Devarapally, Rahul Reddy (Kansas State University, 2016)
Wide bandgap devices have gained increasing attention in the market of power electronics for their ability to perform even in harsh environments. The high voltage blocking and high temperature withstanding capabilities make them outperform existing Silicon devices. They are expected to find places in future traction systems, electric vehicles, LED lightning and renewable energy engineering systems. In spite of several other advantages later mentioned in this paper, WBG devices also face a few challenges which need to be addressed before they can be applied in large scale in industries. Electromagnetic interference and new requirements in packaging methods are some of the challenges being faced by WBG devices. After the commercialization of these devices, many experiments are being carried out to understand and validate their abilities and drawbacks. This paper summarizes the experimental results of various applications of mainly Silicon Carbide (SiC) and Gallium Nitride (GaN) power devices and also includes a section explaining the current challenges for their employment and improvements being made to overcome them.
Keywords: Wide bandgap devices; Silicon Carbide; Gallium Nitride; Inverters; Application